2005
DOI: 10.1016/j.bcp.2005.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Low-molecular-weight fucoidan enhances the proangiogenic phenotype of endothelial progenitor cells

Abstract: Endothelial progenitor cell (EPC) transplantation is a potential means of inducing neovascularization in vivo. However, the number of circulating EPC is relatively small, it may thus be necessary to enhance their proangiogenic properties ex vivo prior to injection in vivo. Fucoidan has previously been shown to potentiate in vitro tube formation by mature endothelial cells in the presence of basic fibroblast growth factor (FGF-2). We therefore examined whether fucoidan, alone or combined with FGF-2, could incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
88
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 31 publications
2
88
0
Order By: Relevance
“…11 ECFC surface expression of ␣6 is upregulated by growth factors, such as vascular endothelial growth factor (VEGF) and fibroblast growth factor 2 12 ; this correlates with enhanced formation of vascular tubes in vitro. 13 To our knowledge, the role of ␣6 expression by ECFCs in adult vasculogenesis has not been investigated. Therefore, we examined the influence of ␣6 expression on the proangiogenic properties of ECFCs and especially on its possible involvement in ECFC recruitment to sites of ischemia.…”
mentioning
confidence: 99%
“…11 ECFC surface expression of ␣6 is upregulated by growth factors, such as vascular endothelial growth factor (VEGF) and fibroblast growth factor 2 12 ; this correlates with enhanced formation of vascular tubes in vitro. 13 To our knowledge, the role of ␣6 expression by ECFCs in adult vasculogenesis has not been investigated. Therefore, we examined the influence of ␣6 expression on the proangiogenic properties of ECFCs and especially on its possible involvement in ECFC recruitment to sites of ischemia.…”
mentioning
confidence: 99%
“…Fucoidan, a high molecular weight sulphated polysaccharide, also favourably enhanced the migratory potential of pre-treated EPCs in vitro. Although alone it did not promote angiogenesis, treatment with fucoidan potentiated the angiogenenic effect of bFGF in EPCs (Zemani et al, 2005). Du et al preconditioned skeletal myoblasts with lithium chloride and showed enhanced cell survival and increased gap-junctional coupling with co-cultured neonatal cardiomyocytes, a result of increased Cx43 expression (Du et al, 2009).…”
Section: Other Agentsmentioning
confidence: 99%
“…Fucoidan, a high molecular weight sulphated polysaccharide, also favourably enhanced the migratory potential of pre-treated EPCs in vitro. Although alone it did not promote angiogenesis, treatment with fucoidan potentiated the angiogenenic effect of bFGF in EPCs (Zemani et al, 2005). Du et al preconditioned skeletal myoblasts with lithium chloride and showed enhanced cell survival and increased gap-junctional coupling with co-cultured neonatal cardiomyocytes, a result of increased Cx43 expression (Du et al, 2009).…”
Section: Other Agentsmentioning
confidence: 99%